POTASSIUM ADSORPTION RATIOS AS AN INDICATOR FOR THE FATE OF AGRICULTURAL POTASSIUM IN GROUNDWATER - Griffioen J. (My University, 2001)
Fertilization of agricultural land in groundwater infiltration areas often causes deterioration of groundwater quality. In addition to nitrogen and phosphorous, potassium deserves attention. The fate of potassium in the subsurface is controlled mainly by cation-exchange. Use of the Potassium Adsorption Ratio (PAR), analogous to the Sodium Adsorption Ratio (SAR) allows one to distinguish between leaching of agricultural potassium to groundwater and desorption of potassium due to increased hardness associated with increased manure spreading on a calcareous soil. Two regional field studies in The Netherlands indicate that groundwater below infiltration areas with agricultural land use, has increased PAR values compared to pristine groundwater in seepage areas and groundwater below infiltration areas with forest. Downward transport of agricultural potassium is retarded compared to conservative chloride due to cation-exchange. In one field study silicate weathering is found to be a potential source for K in pristine groundwater when the residence time is long and easily weatherable silicates, such as glauconite, are present.
Keywords: GROUNDWATER QUALITY; POTASSIUM; AGRICULTURE; CATION-EXCHANGE